2022
DOI: 10.3892/etm.2022.11637
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic value of fractional flow reserve and low‑density non‑calcified plaque based on coronary computed tomography angiography for the identification of lesion‑specific ischemia

Abstract: Increasing evidence has suggested that plaque characteristics are closely associated with ischemia, and coronary computed tomography (CT) angiography-derived fractional flow reserve (FFR CT ) based on deep machine learning algorithms has also been used to identify lesion-specific ischemia. Therefore, the aim of the present study was to explore the predictive ability of plaque characteristics in combination with deep learning-based FFR CT for lesion-specific ischemia. To meet this end, invasive FFR was used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Finally, CAP could be categorized into four stages: stage 0—no plaque (TPV 0, PAV 0); stage 1—mild plaque (a mostly non-obstructive disease; TPV 0–250 mm 3 , PAV 0–5%); stage 2—moderate plaque (a combination of one vessel disease and non-obstructive disease; 250–750 mm 3 , PAV 5–15%); and stage 3—severe plaque (a multivessel disease with majority ischemic; TPV > 750 mm 3 , PAV > 15%) [ 5 ]. Other authors have used CCTA to report similar findings regarding the significance of LD-NCP and plaque characteristics with ischemia [ 6 ]. The study by the ICONIC investigators showed that through CCTA analysis, it was feasible to demonstrate volumetric differences in the composition of CAP, paving the way for the earlier detection of at-risk lesions prior to the future development of ACS [ 7 ].…”
mentioning
confidence: 73%
“…Finally, CAP could be categorized into four stages: stage 0—no plaque (TPV 0, PAV 0); stage 1—mild plaque (a mostly non-obstructive disease; TPV 0–250 mm 3 , PAV 0–5%); stage 2—moderate plaque (a combination of one vessel disease and non-obstructive disease; 250–750 mm 3 , PAV 5–15%); and stage 3—severe plaque (a multivessel disease with majority ischemic; TPV > 750 mm 3 , PAV > 15%) [ 5 ]. Other authors have used CCTA to report similar findings regarding the significance of LD-NCP and plaque characteristics with ischemia [ 6 ]. The study by the ICONIC investigators showed that through CCTA analysis, it was feasible to demonstrate volumetric differences in the composition of CAP, paving the way for the earlier detection of at-risk lesions prior to the future development of ACS [ 7 ].…”
mentioning
confidence: 73%